2001
DOI: 10.1080/02699930125788
|View full text |Cite
|
Sign up to set email alerts
|

Mood-congruent free recall bias in anxiety

Abstract: The present study evaluated the status of mood-congruent free recall bias in anxious individuals following incidental encoding of target words. In the first experiment, high trait anxiety individuals showed increased recall of threat-related information after an orienting task promoting lexical processing of target words. In a second experiment, both lexical and semantic orienting tasks were performed at study. In this experiment, anxious individuals displayed a moodcongruent recall bias only for target inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…This difference was significant even when controlling for the false recall of items that had not been presented during study. These results support the view put forward by Russo, Fox, Bellinger, and Nguyen-Van-Tam (2001) that mood-congruent free recall bias in anxious individuals can be observed if the target material is encoded at a relatively shallow level. Moreover, contrary to Dowens and Calvo (2003), the current results show that the memory advantage for threat-related information in anxious individuals is not a consequence of response bias.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…This difference was significant even when controlling for the false recall of items that had not been presented during study. These results support the view put forward by Russo, Fox, Bellinger, and Nguyen-Van-Tam (2001) that mood-congruent free recall bias in anxious individuals can be observed if the target material is encoded at a relatively shallow level. Moreover, contrary to Dowens and Calvo (2003), the current results show that the memory advantage for threat-related information in anxious individuals is not a consequence of response bias.…”
supporting
confidence: 89%
“…As predicted, Russo et al (2001) did find that high trait anxiety individuals showed greater recall of threat-related information compared to non-anxious individuals following an incidental lexical orienting task that promoted a minimal semantic encoding of targets. Moreover, when both semantic and lexical incidental orienting tasks were used, a mood-congruent free recall bias emerged only for items studied following the lexical orienting task.…”
supporting
confidence: 64%
See 3 more Smart Citations